Diet and adiposity and risk of gastrointestinal cancers in Chinese adults - Chan, WC (2021)
Background: Oesophageal, stomach and colorectal cancers are three major gastrointestinal cancers that together account for approximately 1 million deaths in China annually. Certain dietary factors and adiposity traits have been associated with the risks of these cancers in Western populations, but prospective evidence is still limited in China, where dietary patterns, adiposity levels, and the burden and subtypes of these cancers differ from the West.